Behavior of reinforced earth structures under earthquakes - Kaya, Turgut. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
This study is focused on presenting a literature review and evaluation of types and general concepts of all earth reinforcement structures, especially reinforced earth retaining walls with metallic strip reinforcements, their applications, design methods, components, behavior under seismic loads. Case studies including behavior of structures during previous earthquakes and an example of applied project are investigated. In addition introducing numerical analysis to Reinforced Earth walls and estimating the displacements formed in the structures. Design calculations were carried out for a 6.73m high Reinforced Earth wall, under seismic loading with maximum horizontal acceleration (a0/g = 0.4). By using VALDEZ software which uses limit state approach; solutions including strip length, reinforcement density were determined. Internal and external stability analyses were evaluated. These length and densities were used for 1m width of wall in PLAXIS software. Horizontal and vertical displacements, axial forces on the reinforcements were calculated. The deformations and forces were in the applicable limits. Reinforced Earth structures have proven to be safe and flexible in the presence of seismic events throughout the world. Current design codes apply a very conservative approach, especially in the determination of external stability. A plastic deformation approach be taken instead in the design of Reinforced Earth structures; whereby consideration for seismic design will be based on wall height, ground acceleration, and allowable deformation. The wall height will determine how much reliance needs to be paid to seismic design, with lower height walls being less restrictive than moderate to tall walls.
Keywords: Retaining walls -- Earthquake effects.